Dampak Ekonomi Digital Terhadap Pertumbuhan Umkm Di Era Industri 4.0 - Ndraha, Ayler Beniah; Zebua, Dermawan; Zega, Asokhiwa; Zebua, Mey Kristo (CV. SINAR HOWUHOWU, 2024)
Digital transformation driven by the Industrial Revolution 4.0 has changed the way MSMEs in Indonesia operate and compete in the market. The application of technologies such as e-commerce, big data, and analytics enables MSMEs to improve operational efficiency as well as expand their market reach. This research discusses the impact of the digital economy on MSME growth, as well as the challenges faced, such as a lack of digital literacy and limited infrastructure in rural areas. On the other hand, the Indonesian government has been working to encourage digital transformation through programs such as the National Movement for MSMEs to Go Digital, which provides access to training and technology support. In addition, collaboration between the public and private sectors plays an important role in accelerating technology adoption by MSMEs. The findings show that while the digitalization of MSMEs offers great opportunities to improve productivity and competitiveness, the adoption of these technologies is still constrained by various internal and external factors. Therefore, a holistic and collaborative approach is needed to support MSMEs in the digital transformation process. With comprehensive support, MSMEs are expected to contribute more significantly to the national economy and open up access to global markets. This conclusion shows the importance of a sustainable strategy to facilitate and support the adoption of digitalization in the MSME sector in Indonesia in order to realize inclusive and sustainable economic development.